The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0044-59672011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de resistência à murcha bacteriana em germoplasma de Capsicum spp. do estado do Amazonas

Abstract: A murcha bacteriana, causada por Ralstonia solanacearum, é uma das doenças mais importantes do gênero Capsicum no Brasil. No Amazonas, as condições de elevada temperatura e umidade favorecem o desenvolvimento da doença. O objetivo deste trabalho foi avaliar a resistência à murcha bacteriana de germoplasma, selvagem e comercial, de Capsicum spp. Foram avaliados 22 acessos de Capsicum em casa de vegetação. A inoculação foi feita mediante ferimento das raízes, seguido de adição no solo, ao redor das plantas, de s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Riva-Souza et al (2009) and Moreira et al (2015), evaluating plants at the same time, also confirmed resistance by lower means for the same resistant parent, which were 15.67 and 15.5, respectively. Likewise, Demosthenes and Bentes (2011), evaluating resistance to bacterial wilt in of Capsicum accessions, reported plants with lower AUDPC, being classified as resistant. F 1 , F 2 , BC 1 , and BC 2 showed AUDPC averages close to their susceptible parent (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Riva-Souza et al (2009) and Moreira et al (2015), evaluating plants at the same time, also confirmed resistance by lower means for the same resistant parent, which were 15.67 and 15.5, respectively. Likewise, Demosthenes and Bentes (2011), evaluating resistance to bacterial wilt in of Capsicum accessions, reported plants with lower AUDPC, being classified as resistant. F 1 , F 2 , BC 1 , and BC 2 showed AUDPC averages close to their susceptible parent (Table 1).…”
Section: Resultsmentioning
confidence: 99%